2017
DOI: 10.1080/1331677x.2017.1305803
|View full text |Cite
|
Sign up to set email alerts
|

Monetary freedom and economic growth in New European Union Member States

Abstract: This paper analyses the relationship between monetary freedom (index measured by the Heritage Foundation) and real economic growth of 11 new member states of the European Union. 19-year panel data regression with fixed effects over the period of 1997-2015 reveals that the real GDP growth of the selected countries is positively affected by the degree of monetary freedom. However, the relationship between monetary freedom and real GDP growth has weakened after the global recession of 2008. Monetary freedom was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…An increase in trade freedom by one unit leads toward economic growth by 0.53 percentage point in pre-crises period and it increase to 0.75 percentage point in overall observed period analysis. These finding are in line with the study of Ivanović and Stanišić (2017) which found a positive and robust relationship between trade freedom (TF) and economic growth in both pre-crises period and observed period for new European Union member states. And finally the coefficient of regulations (REGU) is positively significant which means that one unit increases in regulation (REGU) index raises the economic growth by 0.12 percentage point in pre-crises period and 0.80 percentage point in overall observed period.…”
Section: Resultssupporting
confidence: 90%
“…An increase in trade freedom by one unit leads toward economic growth by 0.53 percentage point in pre-crises period and it increase to 0.75 percentage point in overall observed period analysis. These finding are in line with the study of Ivanović and Stanišić (2017) which found a positive and robust relationship between trade freedom (TF) and economic growth in both pre-crises period and observed period for new European Union member states. And finally the coefficient of regulations (REGU) is positively significant which means that one unit increases in regulation (REGU) index raises the economic growth by 0.12 percentage point in pre-crises period and 0.80 percentage point in overall observed period.…”
Section: Resultssupporting
confidence: 90%
“…Bruce and Turnovsky (2013a) have attributed the growth in the economy to demographic factors like fertility, life expectancy, age among others (see Bruce & Turnovsky, 2013b; Yew & Zhang, 2013; Mierau & Turnovsky, 2014; Bloom, Canning, & Sevilla, 2004; Well, 2007). Another strand of studies has created a link between growth and macroeconomic variables, and has also identified different directions of causality between both (Alfaro, Chanda, Kalemli‐Ozcan, & Sayek, 2004; Ivanović & Stanišić, 2017; Prašnikar, Redek, & Drenkovska, 2017; Yülek, 2017). Recently, institutional qualities have also been assigned a chief role in determining economic growth (Acemoglu, Johnson, & Robinson, 2005; Barro, 2003; Bildirici, 2008; Butkiewicz & Yanikkaya, 2006; Chong & Calderon, 2000; Fraj, Hamdaoui, & Maktouf, 2018; Gwartney, Holcombe, & Lawson, 2004; Henderson, Papageorgiou, & Parmeter, 2011; Ji, Magnus, & Wang, 2014; Klein, 2005; Law, Azman‐Saini, & Ibrahim, 2013; Sobel, 2008; Valeriani & Peluso, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…If household and enterprise lending have an independent impact on growth, it might shape our understanding of why the effect of financial development on economic growth varies across countries, as well as provide some important insights regarding the channels through which financial intermediaries stimulate GDP growth (see Beck et al, 2008). Financial repression policies have strong impact on the finance-growth link (Yülek, 2017) as well as monetary freedom (Ivanović & Stanišić, 2017).…”
Section: Introductionmentioning
confidence: 99%